(untitled) (Conversatoria Linguistica, 2019)
The forming process of interactive abilities enables to understand relationships within a social group and to achieve intentions of a speaker. Knowledge about mental and social development of a person can be gained from the structure and process of a dialogue. A dialogue, as a form of the speech therapy, should take account of: different interactive grounds, rules of communication and the intention of an utterance. The function of questions is also important in a conscious usage of a dialogue in the speech therapy. The purpose of this article is to raise awareness that the improvement of both social and communicative competences is possible, despite speech disorders.